Prisoner Guidance Patterns from A Social Work Perspective in Aru Islands Regency Correctional Institutions - Soselisa, Hobarth Williams (Garuda Prestasi Nusantara Consulting, 2024)
Abstract This study aims to determine and analyze the pattern of prisoner development in the perspective of social work in the ARU Islands Regency Correctional Institution. The informants in this study amounted to 5 respondents. The analysis method used in this study is a qualitative descriptive method. The results of the study indicate that the Pattern of Prisoner Guidance in the Perspective of Social Work in the ARU Islands Regency Correctional Institution, as follows, the guidance activities have been carried out well but there are still shortcomings such as lack of budget and facilities in supporting the established guidance program. Some prisoners are less interested or not motivated to participate in the training program. Prisoners have diverse backgrounds, abilities, and needs, which require a flexible and varied training approach. Some inmates feel reluctant or distrustful of relationship-building efforts. Families and communities show distrust or reluctance to accept inmates back. Keywords : Social Worker Development Patterns and Perspectives.